The cost of the inpatient management of febrile neutropenia in cancer patients – a micro‐costing study in the Irish healthcare setting. (29th January 2014) - O'Brien, C.; Fogarty, E.; Walsh, C.; Dempsey, O.; Barry, M.; Kennedy, M.J.; McCullagh, L.
<x xml:space="preserve">Abstract</x> The objective was to evaluate the resource use and cost of hospitalisation for febrile neutropenia (FN) from the health‐payer's perspective. This was a single centre study. Adults undergoing chemotherapy, who were admitted for FN, were identified prospectively. Patient medical records were reviewed retrospectively. Demographics and resource utilisation data were obtained from a cohort of 32 patients (69% female, mean age = 58.8 years). Twenty‐five per cent of patients had more than one FN episode. In total, 42 FN episodes were captured; 60% of episodes had occurred within the first two cycles of chemotherapy. The bootstrap estimation was used to determine mean hospital length of stay (LOS) with standard deviation (±SD) and mean costs ± SD. The mean LOS was 7.3 ± 0.5 days. The mean cost per FN episode was €8915 ± 718. The major cost driver was hospital bed‐stay (mean cost of €6851 ± 549). Other cost drivers included antibacterial treatment at €760 ± 156, laboratory investigations at €538 ± 47 and the requirement for blood bank products at €525 ± 189. To our knowledge, this is the first investigation of the cost of chemotherapy induced FN within the context of the Irish healthcare setting.